2015
DOI: 10.3141/2509-04
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of Recycled Pavement Foundation Layers

Abstract: This paper describes results from a study comparing the performance of side-by-side test sections of pavement foundation layers constructed with on-site recycled materials and surfaced with hot-mix asphalt (HMA). Test sections included recycled materials blended with subgrade to create a mechanically stabilized subgrade layer and recycled materials placed in an overexcavated subgrade layer. In situ falling weight deflectometer (FWD), dynamic cone penetrometer (DCP), and laboratory freeze–thaw tests were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In summary, these laboratory findings indicated that seasonal freeze-thaw cycles had a significant effect on weakening the mechanical properties of pavement foundation materials, including unstabilized and stabilized recycled pavement materials. On the other hand, there are fewer field studies studying the recycled pavement materials as pavement foundations under seasonal freeze-thaw cycles [28,38]. The field test results matched the laboratory freeze-thaw test results [30,38].…”
Section: Introduction 1general Backgroundmentioning
confidence: 72%
See 1 more Smart Citation
“…In summary, these laboratory findings indicated that seasonal freeze-thaw cycles had a significant effect on weakening the mechanical properties of pavement foundation materials, including unstabilized and stabilized recycled pavement materials. On the other hand, there are fewer field studies studying the recycled pavement materials as pavement foundations under seasonal freeze-thaw cycles [28,38]. The field test results matched the laboratory freeze-thaw test results [30,38].…”
Section: Introduction 1general Backgroundmentioning
confidence: 72%
“…The main difference between cold and hot recycling techniques refers to whether the existing bitumen in recycled materials is heated to restore its viscosity prior to compacting [23,24]. Overall, the investigated topics of these studies on recycled pavement materials are categorized into three aspects: (i) characterizing the mechanical properties, such the strength and stiffness that may represent the capacity to bear traffic loading [25,26]; (ii) evaluating their durability to freeze-thaw and wet-dry cycles [27,28]; and (iii) environmental impacts such as the leaching of metals and high alkalinity and pH [29,30]. Generally, findings from these laboratory investigations demonstrated that recycled pavement materials are able to provide comparable performance to normally used aggregate base materials, such as crushed limestone and granite [31][32][33][34][35][36].…”
Section: Introduction 1general Backgroundmentioning
confidence: 99%